Effects of exposure to ambient ultrafine particles on respiratory health and systemic inflammation in children. (May 2018) - Clifford, Sam; Mazaheri, Mandana; Salimi, Farhad; Ezz, Wafaa Nabil; Yeganeh, Bijan; Low-Choy, Samantha; Walker, Katy; Mengersen, Kerrie; Marks, Guy B.; Morawska, Lidia
Abstract: It is known that ultrafine particles (UFP, particles smaller than 0.1 μm) can penetrate deep into the lungs and potentially have adverse health effects. However, epidemiological data on the health effects of UFP is limited. Therefore, our objective was to test the hypothesis that exposure to UFPs is associated with respiratory health status and systemic inflammation among children aged 8 to 11 years. We conducted a cross-sectional study among 655 children (43.3% male) attending 25 primary (elementary) schools in the Brisbane Metropolitan Area, Australia. Ultrafine particle number concentration (PNC) was measured at each school and modelled at homes using Land Use Regression to derive exposure estimates. Health outcomes were respiratory symptoms and diagnoses, measured by parent-completed questionnaire, spirometric lung function, exhaled nitric oxide (FeNO), and serum C reactive protein (CRP). Exposure-response models, adjusted for potential personal and environmental confounders measured at the individual, home and school level, were fitted using Bayesian methods. PNC was not independently associated with respiratory symptoms, asthma diagnosis or spirometric lung function. However, PNC was positively associated with an increase in CRP (1.188-fold change per 1000 UFP cm −3 day/day (95% credible interval 1.077 to 1.299)) and an increase in FeNO among atopic participants (1.054 fold change per 1000 UFP cm −3 day/day (95% CrI 1.005 to 1.106)). UFPs do not affect respiratory health outcomes in children but do have systemic effects, detected here in the form of a positive association with a biomarker for systemic inflammation. This is consistent with the known propensity of UFPs to penetrate deep into the lung and circulatory system. Highlights: Epidemiological evidence on ultrafine particles (UFP) and human health is limited. Only a handful of studies investigating the health impact of UFP in children. We conducted a cross-sectional study among 655 children from 25 primary schools. UFP do not affect respiratory health in children but do have systematic effects. We showed a positive association with a biomarker for systemic inflammation.